ANALISIS KEBUTUHAN PENGEMBANGAN INSTRUMEN PENILAIAN PROGRAM LITERASI MEMBACA BAGI SMA CAMBRIDGE SCHOOL - Wahyu Lestari; Nurul Hidayah (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
A survey conducted by PISA released by OECED in 2019 resulted in Indonesia's literacy rate being number 62 out of 70 countries. This means that the reading interest of the Indonesian people is very alarming. Moving on from that, educational institutions play an essential role in implementing literacy programs that increase reading interest. In his assessment, the author has not found the development of the instrument. Developing an assessment instrument in a reading literacy program requires a needs analysis. Needs analysis is used to identify the reading literacy program's objectives and the program's conditions empirically. So that analytical research was conducted to determine the need for instrument development and find solutions for the appropriate literacy program assessment instrument for SMA Kesatuan Bangsa Yogyakarta students. The basis for developing the device is a needs analysis in analyzing using research methods. The method used is a qualitative research method. The data collection technique is observation, interview, and documentation—primary and secondary data sources. Primary data sources are high school students, and secondary data comes from teachers. This method produces a needs analysis for developing instruments to measure literacy programs that occur from what they aspire to. The study results convey that the needs analysis contains the achievements and needs in the preparation of the assessment instrument. Based on the study results, the conclusions obtained are the need to develop an assessment instrument for reading literacy programs as a tool for measuring existing problems. The device is expected to make positive and valuable changes